A Narrative Research of an EFL Student’s Speaking Learning Strategy - Arilia Triyoga; Halimatu’ Sa’diyah; Ratri Nur Hidayati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Speaking is an interactive process of constructing meaning that involves producing, receiving, and processing information or expressing one's thoughts and feelings in spoken language. For most people, mastering speaking skills is the most critical aspect of learning a foreign language. Success is measured by the ability to converse in that language. Some students are successful in learning to speak, and others find challenges. This study aims to explain experiences of the student’s speaking learning strategies employed by a high-performance student using narrative study. This study employed Narrative research by interviewing a seventh-semester student who is considered a successful learner because he has a high English Proficiency Score and an advanced speaking skill level. To check the data's trustworthiness, the researcher did member checking. As a result, the participant employed a memory learning strategy by using images and sound.